Hubungan Perilaku Caring Perawat Dengan Stres Pasien di Ruang Isolasi Covid-19 Rumah Sakit Qolbu Insan Mulia Kabupaten Batang - Nurdianto Nurdianto; Isrofah Isrofah; Nonik Eka Martyastuti (PENA NURSING, 2023)
The nursing profession will be very proactive in playing a central role ini providing nusing service during the covid-19 pandemic. Caring behavior in providing care will decrease if the nurse are under stress. Covid-19 patient undergoing isolation in hospitals experience stress due separated from family.  The aim to determine correlation  of nurse caring behaviour to patient stress in Covid Isolation Room Qolbu Insan Mulia Hospital, Batang Regency. This research design used descriptive correlation with cross sectional approach. Samples were patient who hospitalization in the isolation Qolbu Insan Mulia Hospital, Batang Regency as many as 20 people by accidental sampling. The research instrument questionare.  Data were analyzed used chi square. There was correlation  of nurse caring behaviour to patient stress in Covid Isolation Room Qolbu Insan Mulia Hospital, Batang Regency with r value 0,020. Nurses should improve nursing behaviour in providing nursing care to Covid-19 patient in isolation room, because patient are risk get stress.